Next-generation DNA sequencing shows a microbiota shift after an incursion of Pseudomonas syringae pv. actinidiae (Psa) on a single kiwifruit orchard - Pushparajah, I.P. Shamini; Jones, Daniel F.; Everett, Kerry R. (New Zealand Plant Protection, 2019)
A virulent strain of Pseudomonas syringae pv. actinidiae (Psa) is a major pathogen for New Zealand’s 3B kiwifruit (Actinidia spp.) industry, and was first identified from a Te Puke orchard on 5 November 2010. Psa was first found on the Kerikeri research orchard (KRO) of Plant & Food Research on 19 September 2014. The samples for this study were collected from the same orchard on 7 December 2012 and 25 November 2014, i.e. before and after the Psa incursion. Polymerase chain reaction (PCR) was conducted on total genomic DNA from four leaf discs of 15 individual vines sampled from two kiwifruit cv. ‘Hort16A’ orchard blocks at KRO, using modified PCR primers complementary to bacterial 16S ribosomal DNA and the fungal inter-transcribed spacer (ITS) region. The microbiota present before and after the Psa incursion were investigated by Illumina MiSeq™ next-generation sequencing to produce 2 × 300 bp pair end reads, followed by metabarcoding analysis using QIIME2 software. Populations of fungi from the Basidiomycete orders Filobasidiales, Sporidiobolales, Tremellales and Leucosporidiales, and genera of bacteria with known biological control activity, such as Erwinia, Pantoea, Methylobacterium, Sphingomonas and Paenibacillus, increased in the presence of Psa.